THE EFFECT OF RED SWEET POTATO (Ipomoea batatas L.) SUBSTITUTION ON SKIM MILK AS PREBIOTIC ON SYNBIOTIC DRINK POWDER CHARACTERISTIC - Edhi Nurhartadi, Ratih Nawangwulan, Rohula Utami, (Proceeding of International Congress, 2014)
Red sweet potato (Ipomoea batatas L.) is known as a source of prebiotic because it contains oligosaccharideraffinose. Usage of prebiotic along with probiotic known as synbiotic. Powdered fermented synbioticdrink is one of the fermented drink diversification. The aim of this research was to study the effect of formulationratio of red sweet potato filtrate (RSPF) and skim milk (SM) on probiotic bacterial count, physicochemicaland sensory characteristic of synbiotic drink powder that dried using spray dryer.Formulation ratio of RSPF:SM = 75%:25% (F1), 50%:50% (F2), and 25%:75% (F3). Formulation ratio of RSPFand SM showed effect on pH, microencapsulation efficiency, solubility, and sensory properties. Lowest pHvalue (4.55), highest microencapsulation efficiency (4.47%) obtained from the formulation of 75% RSPFand 25% SM. Highest solubility obtained from the formulation of 50% RSPF and 50% SM. Based on sensoryanalysis, formulation of 75% RSPF and 25% SM had the highest sensory properties with âneutralâaroma (3.20); âneutralâ flavor (3.3); and âlikeâ overall (3.50).Keywords: fermented drink, raffinose, red sweet potato, spray drying, synbiotic